Tropical deforestation a socio-economic approach (London Earthscan, 2009)
Deforestation - A Socio-Economic Approach offers a new perspective on the economic imperatives which encourage indigenous populations to encroach upon their own forests, and shows how action against deforestation must form part of a wider movement to improve both the living conditions of the local inhabitants and the durability of their national economies. Part 1 offers an overview of the processes surrounding deforestation, and an assessment of the current situation. Part 2 analyses the land-use issues, and explains the socioeconomic imperatives in the affected regions. In an absorbing conclusion. Part 3 guides the reader through a series of hypothetical policy scenarios, using a specially adapted economic computer model, to predict which combinations of policies and trade arrangements might bring about a more beneficial state of affairs.
Includes bibliographical references and index.
Keywords: Deforestation -Tropics.